La sistematización de la biblioteca de la unidad educativa “Victoria Vásconez Cuvi” de la ciudad de Latacunga y su incidencia en la organización científica técnica para mejorar los servicios en el período 2013-2014 - Tigse Osorio, Eva Piedad (2014)
This work called "THE "VICTORIA VÁSCONES CUVI" LIBRARY SYSTEMATIZATION LATACUNGA CITY AND ITS IMPACT ON THE SCIENTIFIC - TECHNIQUE ORGANIZATION TO IMPROVE SERVICES FOR THE PERIOD 2013 - 2014". The general objective of the research involved is the right way to apply the laws rules and regulations of existing documents in the library of the educational unit "Victoria Vásconez Cuvi" Latacunga city The methods used for the following research were: Inductive, Deductive and analytical. The techniques and instruments were applied to the survey both students and teachers corresponding to 28 professionals and students in a number of 60, which provided them with valuable information. After analyzing the data from the field investigation has determined that in question # 1 74.4% seek literature searches literature on the race remaining no; 65% stated that the library if it meets your needs readers, 34% said no; 46.5 states that enjoys reading, while 53, 4% said no;, 38.6% say that if you visit the library and 61.3% do not; 42% of respondents say they agree with the current system while 57.9% said no; state that engaged in reading between 1 and 4h00 and finally 82.9% don’t have a home library while the rest have it.